Oral Schwannoma—An Unusual Oral Presentation: Case Report and Literature Review - Arwade, Reena Vardhaman; Prakash, Nimish; Karjodkar, Freny; Sansare, Kaustubh; Desai, Rajiv; Bhuta, Bansari (Journal of Orofacial Research, 2014)
Schwannoma or neurilemmoma is benign, slow growing, usually solitary and encapsulated tumor, originating from schwann cells of the nerve sheath. Intraoral schwannoma accounts for 1% of head and neck region and commonly involves tongue. Most of the earlier reports in the literature, have described schwannomas that occurred in the tongue. In this article, we report a case of schwannoma involving an unusual site - mandibular labial vestibule, in a young patient. The lesion was completely excised with no reported complication for a followup of 15 months.